Implementing Game-Based Learning to Improve Students' Collaboration and Learning Outcomes on Work, Energy, and Simple Machines - Aprilia Wulandari; M. Hidayat; Erlida Amnie (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2026)
This study aims to describe the implementation of Game-Based Learning (GBL) assisted by Kahoot and to analyze the improvement of students' collaboration skills and learning outcomes on the topic of work, energy, and simple machines in class VIII A of SMP Adhyaksa 1 Jambi. This research employed Classroom Action Research conducted in two cycles consisting of planning, action, observation, and reflection stages. The research subjects were 17 students. Data were collected through collaboration observation sheets and learning achievement tests, then analyzed descriptively and inferentially. The results showed that students' collaboration skills improved from 50.81% in Cycle I to 63.83% in Cycle II, categorized as good. Learning outcomes also showed significant differences based on the Friedman test (x²(2) = 13.447; p < 0.05). The paired sample t-test, which was conducted to evaluate students' learning outcomes, indicated a significant difference between the initial and final collaboration scores, with a Cohen's d effect size of 1.42 (large category). These findings indicate that the implementation of GBL assisted by Kahoot is effective in enhancing students' collaboration skills and learning outcomes. Therefore, this approach can serve as an innovative instructional strategy in physics learning at the junior high school level.